2003
DOI: 10.1159/000072168
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial of an Air-Abrasion/Chemomechanical Operative Procedure for the Restorative Treatment of Dental Patients

Abstract: The aim of this study was to investigate whether caries removal with air-abrasion/Carisolv™ gel is an acceptable and viable alternative in the treatment of dental patients. Twenty-two patients were treated with conventional methods (local anaesthetic injection/drill) followed by alternative treatment (air-abrasion and Carisolv gel) in a general practice setting, by the same operator. The participants’ pre-operative anxiety levels were measured using the Modified Dental Anxiety Scale. Their postoperative levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 16 publications
2
40
0
6
Order By: Relevance
“…However, one paper from the UK did find that air abrasion produced appreciably less pain and anxiety than the use of local anaesthetic and drill. 134 The study reported that the most welcome aspect of air abrasion was that it was pain-free, quick, avoided unpleasant aspects of the drill such as the noise and vibrations, and that it avoided local anaesthetic injection and continued numbness, which have been found to be sources of considerable anxiety. 135 …”
Section: Alternative Methods For Tooth Preparationmentioning
confidence: 99%
“…However, one paper from the UK did find that air abrasion produced appreciably less pain and anxiety than the use of local anaesthetic and drill. 134 The study reported that the most welcome aspect of air abrasion was that it was pain-free, quick, avoided unpleasant aspects of the drill such as the noise and vibrations, and that it avoided local anaesthetic injection and continued numbness, which have been found to be sources of considerable anxiety. 135 …”
Section: Alternative Methods For Tooth Preparationmentioning
confidence: 99%
“…Nonetheless, the method may be suitable for caries management, since anesthesia could be avoided, 9,11 thus compensating for the time required for anesthesia injection and onset of anesthesia as well as for time needed for behavior management. 17,18 In addition, caries removal by CMCR in indirect pulp therapy could decrease the risk of mechanical pulp exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ideal in caries removal is to excavate the diseased dentine to the junction between these two layers [Banerjee et al, 2000c], as opposed to removing all demineralised dentine, as the operator in this study has done over most of the surface area of the 10 carious lesions. Banerjee and co-workers have investigated a number of techniques in caries excavation including hand and rotary bur excavation, air abrasion, sono-abrasion, chemomechanical caries removal, laser and enzyme [Banerjee et al, 2000a, b;Rafique et al, 2003]. A new polymer bur [Boston, 2003], which was claimed to remove infected dentine only, has also been investigated [Celiberti et al, 2006].…”
Section: Removal Of Dentinementioning
confidence: 99%